2D Doping of Proton Conductors: BaZrO3‐Based Heterostructures. Issue 4 (18th December 2020) - Ngabonziza, Prosper; Merkle, Rotraut; Wang, Yi; van Aken, Peter A.; Bjørheim, Tor S.; Maier, Joachim; Mannhart, Jochen
Abstract: Ionically conducting oxide heterostructures provide ideal geometries for revealing interfacial effects in solid state ionics. Beyond that, they can provide a high density of heterointerfaces and thus allow for reliable studies of interfacial phenomena with respect to fundamental understanding as well as with respect to nanoionic applications. Substituting an entire single layer rather than random single ions by aliovalent impurities enables the possibility of 2D doping rather than conventional 0D doping. To the best of the authors' knowledge, this technique has never been applied to ionically conducting systems. Acceptor‐doped barium zirconate has been widely investigated, particularly for applications in clean energy technologies, most importantly for intermediate temperature fuel cells. Here, epitaxial BaZrO3 –BaYO x heterostructures and in particular 2D doping of BaZrO3 by yttrium are reported. The effects on proton conductivity are studied. The results not only lead to fundamental insight into the pros and cons of 2D doping of ion conductors, but may also help improve protonic devices. Abstract : Thin films of BaZrO3 are prepared by pulsed layer deposition and isolated, single Zr–O layers replaced by Y–O layers. This technique of producing charge carriers in the intermediate vicinity is called "2D doping." After hydration, these films show significant proton conductivity. Pros and cons are discussed in comparison with the conventional homogeneous doping.